Volume 6: Structures and Dynamics, Parts a and B 2009
DOI: 10.1115/gt2009-59598
|View full text |Cite
|
Sign up to set email alerts
|

Cracked Blade Detection From Bladed Disk Forced Response

Abstract: The primary task of this study is to offer reliable and accurate model of a bladed disk containing cracked blade. This model allows simulation of bladed disk dynamic behavior for various crack positions and lengths. Due to absence of cyclic symmetry caused by crack presence in the disk, a reduction procedure was implemented to simulate full bladed disk. It is proposed to use crack location as an interface between two substructures for subsequent fixed-interface method application. Harmonic balance method was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Secondly, it makes rotate a mode even in the case of standing wave excitation. This feature vanishes at the presence of mistuning (depending on its level [10]). Also, as shown experimentally, because of mistuning, a standing wave of response can appear at a…”
Section: Fig 27 Representative Scheme Of Pzt Excitation Simulation 4mentioning
confidence: 97%
“…Secondly, it makes rotate a mode even in the case of standing wave excitation. This feature vanishes at the presence of mistuning (depending on its level [10]). Also, as shown experimentally, because of mistuning, a standing wave of response can appear at a…”
Section: Fig 27 Representative Scheme Of Pzt Excitation Simulation 4mentioning
confidence: 97%
“…They revealed that there can be a cracked-blade-localized vibration response for some families of modes. Kharyton et al 22 also investigated the effects of a cracked blade on the vibration response of a bladed disk without blade-to-blade mistuning.…”
Section: Introductionmentioning
confidence: 99%
“…Later on, The contact model in the Finite Element Method (FEM) is adopted to obtain the breathing effects of the cracked blade [23][24][25]. An additional force vector is formed in the contact model to simulate the effect of crack closure, where the force vector is displacement-dependent and time-varying [24]. As a result, the equations of motion with alternating loads are nonlinear and difficult to solve.…”
mentioning
confidence: 99%
“…The contact model is applied in the beam model with effects of loads taken into account [22]. Later on, The contact model in the Finite Element Method (FEM) is adopted to obtain the breathing effects of the cracked blade [23][24][25]. An additional force vector is formed in the contact model to simulate the effect of crack closure, where the force vector is displacement-dependent and time-varying [24].…”
mentioning
confidence: 99%